2019
DOI: 10.3341/kjo.2019.0065
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Focal and Conventional Verteporfin Photodynamic Therapy for Chronic Central Serous Chorioretinopathy

Abstract: PurposeTo evaluate the efficacy of focal verteporfin photodynamic therapy (PDT) in patients diagnosed with chronic central serous chorioretinopathy (CSC).MethodsThis study enrolled 52 eyes of 52 patients with chronic CSC who had received verteporfin PDT. The laser spot size of 26 eyes covering only the localized hyperfluorescent area in indocyanine green angiography was classified as focal PDT. The PDT spot size of the other 26 eyes covered the total area of retinal pigment epithelial detachment including the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…Complications of PDT in cCSC were rarely reported; in detail no serious adverse event related to PDT administration was described. CNV occurred in a total of 4 cases [10,20], secondary RPE atrophy was described in the 7% of cases by Noh [18], and RPE hyperplasia was identified in 9/72 subjects by Moreno [20]. In the other studies, no complication related to PDT session or PDT effects was reported in 4 studies, whereas no specific data was presented in 6 studies.…”
Section: Standard Pdtmentioning
confidence: 96%
See 1 more Smart Citation
“…Complications of PDT in cCSC were rarely reported; in detail no serious adverse event related to PDT administration was described. CNV occurred in a total of 4 cases [10,20], secondary RPE atrophy was described in the 7% of cases by Noh [18], and RPE hyperplasia was identified in 9/72 subjects by Moreno [20]. In the other studies, no complication related to PDT session or PDT effects was reported in 4 studies, whereas no specific data was presented in 6 studies.…”
Section: Standard Pdtmentioning
confidence: 96%
“…Overall, follow-up ranged between 1 and 5 years with 8/13 studies with 1-year follow-up and 4/13 with prospective design [10,11,[17][18][19][20][21][22][23][24][25][26][27] (Table 1).…”
Section: Standard Pdtmentioning
confidence: 99%
“…Although the pathogenesis of CSC has not yet been identified, several hypotheses have been proposed to explain it such as the alteration of the outer blood-retinal barrier, the function of the RPE pump due to defective choroidal circulation,[ 31 32 ] and mechanical obstructions of the vortex vein. [ 33 34 ] Two studies have shown asymmetrical dilatation of the vortex vein in patients with CSC.…”
Section: Pathogenesismentioning
confidence: 99%
“…[ 31 ] Furthermore, to decrease the risk of complications, a study was conducted on PDT spot size. [ 32 ] Noh et al . reported that focal verteporfin PDT, confined to areas of localized leakage demonstrated in ICGA compared with conventional verteporfin PDT, covered the total area of abnormal choroidal vessels, including the leakage, resulting in a significant decrease in SRF and subfoveal choroidal thickness as well as conventional PDT during the 1-year follow-up.…”
Section: Photodynamic Therapymentioning
confidence: 99%
See 1 more Smart Citation